Determinants of Cooperative Residual Business Results - Wachidah Fauziyanti; Tiara Nove Ria (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to determine the effect of the number of members, member savings and member loans on the residual business results (Sisa Hasil Usaha/SHU) of Memayu Jogo Tonggo Kopeng Cooperative, Semarang district. The population in this research is cooperative financial reports. The sample was selected using a purposive random sampling method. The sampling was taken in 2021-2023 for three years. The results of the Multiple Linear Regression analysis show that the variable number of members significantly affects SHU with a calculated t value of 2.792 with a significance value of 0.016 <0.05. The member savings variable does not substantially affect SHU, with a computed t-value of 1.542 and a significance value of 0.130 > 0.05. The member loans variable significantly affects SHU with a calculated t value of 3.836 with a significance value of 0.000 <0.05. The variables number of members, member savings and member loans have a significant effect simultaneously or together on SHU with a calculated f value of 9.619 with a significance level of 0.000 < 0.05. The suggestion from this research is that future researchers can find other independent variables that can influence the dependent variable and increase the sample by extending the research period.